Evaluation of Oral Preparations of Vitamin E as Antioxidant Using DPPH Method (Diphenyl picrylhydrazyl) - Broto Anung Laksono; Nawal Ariqoh Rif'at; Tsabitah ‘Afiy Arsyah; Erlisa Alya Hanifah; Evi Wiela Astuti; Happy Rizki Rakhmawati; Clarisa Dian Cahyani; Hanun Najwa; Ariesta Yusuf Adyatama; Dena Septiyani; Zabrina Izatti Rachman; Agda Rismafuri Mukti Kirana; Achmad Toto Purnomo; Retno Sari (Universitas Airlangga, 2023)
This article aimed to evaluate the activity of Vitamin E as an antioxidant in oral pharmaceutical preparations. Vitamin E was an essential nutrient soluble in fat that had the pharmacological effect as an antioxidant. Vitamin E consisted of α, β, γ, δ-tocopherol and α, β, γ, δ-tocotrienol. The activity of Vitamin E was observed for its ability to inhibit reduction using the DPPH method. The antioxidant activity was calculated as an inhibition concentration of 50% (IC50), which was the concentration of a sample that could reduce 50% of DPPH. It was known that IC50 of Vitamin E was very strong with a value of 42,86%. Based on the article review, it could be concluded that the activity of Vitamin E as an antioxidant in oral pharmaceutical preparations was very high and strong. Keywords: Vitamin E, Alpha-Tocopherol, Antioxidant, Activity, IC50, Oral Pharmaceutical Preparations